Controllable synthesis of ultrathin Co9S8 nanosheets as a highly efficient electrocatalyst for overall water splitting. (10th August 2018) - Yang, Yan; Yuan, Mengwei; Li, Huifeng; Sun, Genban; Ma, Shulan
Abstract: A facile and convenient hydrothermal method was employed to synthesize cobalt sulfides with different controllable morphologies by varying the filling factor, and ultrathin Co9 S8 nanosheets (∼3 nm) were obtained with the autoclave filled up to 60%. For the first time the electrocatalytic performance of the ultrathin Co9 S8 nanosheets for both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) was investigated. Benefiting from the larger electrochemical active surface area and more exposed accessible active sites, the ultrathin Co9 S8 nanosheets, meanwhile, presented a remarkable performance towards OER and excellent catalytic activity for the HER process. To reach a current density of 10 mA cm −2, the overpotential is only 206 mV for OER in 1.0 M KOH, which is very close to RuO2 (200 mV). For HER, a low overpotential of only 178 mV is needed to reach 10 mA cm −2 in 0.5 M H2 SO4 . This work may inspire the development of low-cost, efficient electrocatalysts for energy conversion with ultrathin Co9 S8 nanosheets. Graphical abstract: Controllable synthesis of ultrathin Co9 S8 nanosheets as low-cost, efficient electrocatalyst for both OER and HER. Image 1